2015
DOI: 10.1007/s10336-015-1196-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of light pollution on biological rhythms of birds: an integrated, mechanistic perspective

Abstract: Light pollution is considered a threat for biodiversity given the extent to which it can affect a vast number of behavioral and physiological processes in several species. This comes as no surprise as light is a fundamental, environmental cue through which organisms time their daily and seasonal activities, and alterations in the light environment have been found to affect profoundly the synchronization of the circadian clock, the endogenous mechanism that tracks and predicts variation in the external light/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 83 publications
1
66
0
2
Order By: Relevance
“…The choice of such light colors was made to cover both short (green) and long wavelengths (red), as well as the broad-spectrum white light. Because sensitivity to light in birds' photoreceptors peaks at mid-short wavelengths (Peirson et al, 2009;Hunt et al, 2014;Dominoni, 2015), we expected white and green light to be associated with stronger responses than red light and the dark treatment. Specifically, we predicted that white ALAN would increase DEE in great tits, because in previous studies we have found that white ALAN was associated with increased provisioning rate during the day (Titulaer et al, 2012), as well as with higher activity levels at night (Ouyang et al, in press), but they never directly measured energy expenditure.…”
Section: Introductionmentioning
confidence: 95%
“…The choice of such light colors was made to cover both short (green) and long wavelengths (red), as well as the broad-spectrum white light. Because sensitivity to light in birds' photoreceptors peaks at mid-short wavelengths (Peirson et al, 2009;Hunt et al, 2014;Dominoni, 2015), we expected white and green light to be associated with stronger responses than red light and the dark treatment. Specifically, we predicted that white ALAN would increase DEE in great tits, because in previous studies we have found that white ALAN was associated with increased provisioning rate during the day (Titulaer et al, 2012), as well as with higher activity levels at night (Ouyang et al, in press), but they never directly measured energy expenditure.…”
Section: Introductionmentioning
confidence: 95%
“…Such a drop was related at the individual level to the amount of activity that a bird showed in the morning, regardless of the origin of the animal (urban versus forest). This suggests that light at night, via changes in melatonin levels, can promote the emergence of early chronotypes, which could be favoured in urban environments [74,97]. This hypothesis requires further testing, but the availability of novel molecular tools might inspire further studies [98].…”
Section: Timing As a Sexually Selected Trait In Birds (A) Daily Timingmentioning
confidence: 99%
“…In addition, other manipulations of the natural light/ dark cycle (e.g. use of artificial light at night in natural habitat) are possible [90] and have been shown to affect circadian as well as seasonal traits in a variety of species [91][92][93]. However, the fitness consequences of such effects are still unclear.…”
Section: Resultsmentioning
confidence: 99%